Transforming Citizen Engagement In E- Governance Framework: A Conceptual Analysis - Araby, Mohamed Awad Ali Al (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2024)
This study offers a conceptual and critical analysis of how citizen engagement has evolved within the e-governance framework, emphasizing the transition from traditional public administration to New Public Governance (NPG) in the digital era. By mapping four waves of governance transformation—from hierarchical bureaucracies to smart governance—the article highlights the redefinition of citizens' roles from passive service recipients to proactive partners in public service co-production. Drawing on international best practices, including from Japan, Norway, and the UK, the study identifies the determinants of effective digital participation, such as ICT infrastructure, policy design, and civic readiness. The key finding is that meaningful e-participation is contingent on both the supply side (government initiatives and digital tools) and the demand side (citizen willingness and digital literacy), forming a two-way governance relationship. The research proposes a model of “Smart Citizen Governance” that integrates co-decision, co-implementation, and co-evaluation as central pillars of inclusive and sustainable public service delivery. This analysis is especially relevant for non-Western public administration contexts, where digital transformation intersects with diverse institutional traditions and citizen expectations. By addressing existing research gaps in digital governance and citizen empowerment, the article contributes to the broader discourse on public sector reform, democratic innovation, and local policy effectiveness in the Global South.